Analisis Kelayakan Pemasangan Load Break Switch (LBS) Penyulang Rindik pada Proses Manuver Antar Penyulang di PLN ULP Toboali - Syarifah; Kurniawan, Rudy; Asmar (ELECTRON Jurnal Ilmiah Teknik Elektro, 2021)
The electric power distribution system is very important for the distribution of electricity to consumers, especially for the continuity of voltage and power services. Currently, due to the maintenance / maintenance of Circuit Breakers in the Rindik feeders, it is necessary to maneuver the load by installing an LBS Load Break Switch (LBS) between the two feeders. From that it is necessary to do an analysis of the power flow between the existing conditions and after the maneuver, obtained based on the Software Simulation in the first condition seen from the end voltage of the Bencah feeder, which is 19,423 kV, with power losses of 0.129 MW. The results of the second condition power flow can be seen at the tip voltage at the Bencah feeder, which is 18,153 kV with a power loss of 0.294 MW. And the simulation results. The third condition of the power flow can be seen from the tip of the Bencah feeder and the City turtle, the value of the end of the Bencah feeder is 18,969 kV and the tip voltage at the City feeder is 19,395 kV with a total power loss of 0.304 MW. Judging from the results of the 3 simulation simulation results, the maneuvering load that produces a good end voltage, and has the most small power losses, is in the first condition maneuver simulation so that it can be stated Load Brek Switch (LBS) Gang asem the first condition is feasible to install.